Mechanization outsourcing services in Myanmar's dry zone - Belton, Ben; Fang, Peixun; Reardon, Thomas (Michigan State University, 2020)
Outsourcing enterprises that rent out agricultural machinery with operators to farm households have been vital to facilitating rapid agricultural mechanization in Myanmar over the past five years. This report presents results from the first ever study of agricultural machinery outsourcers in Myanmar. One hundred and twenty two outsourcing enterprises were surveyed in 12 Dry Zone townships in December 2017. These included 79 enterprises providing four-wheel tractor (4WT) outsourcing services, 32 providing combine harvester (CH) services, and 11 offering both CH and 4WT services. The following results stand out: Outsourcing of CH and 4WT services is a recent phenomenon, and has expanded extremely rapidly: 88% of 4WT and 94% of CH owned by surveyed outsourcers were purchased during or after 2014. However, purchases of both 4WT and CH slowed in 2017, suggesting that market maturation is beginning. The total area harvested by CH outsourcing enterprises grew 1240% from 2013 to 2017, while that serviced by 4WT outsourcers grew 900%. The average area of land harvested by each CH outsourcing enterprise annually grew from 101 ha in 2013 to 114 ha in 2015, shrinking thereafter as greater competition emerged, to reach 86 ha in 2017. The average area of land worked by 4WT outsourcers was stable from at around 150 ha from 2014 onwards. Agricultural machinery outsourcing enterprises are small businesses. The vast majority own a single machine and are also farmers. Their farms are toward the upper end of the farm size distribution, but they are not large landowners or companies. Agricultural machines were purchased mainly from private machinery supply businesses. This was the case for all CH, and three-quarters of 4WT, despite government efforts to promote tractor sales through the Department of Cooperatives. Machine purchases have been facilitated by access to formal finance. Two-thirds (64%) of CH and just over half (54%) of 4WT were purchased using financing from a bank or machinery dealership. Purchases of 4WT made using credit obtained from government sources accounted for 19% of sales. The introduction of transferrable land use rights (Form 7) has facilitated access to formal finance. Form 7 was used to guarantee almost all machinery loans provided by banks. Provision of outsourcing services is highly profitable. Most of the capital costs of CH outsourcing enterprises can be recovered within two years. Repayment periods are slightly longer for 4WT outsourcing enterprises, but almost all 4WT outsourcers were able to repay loans in full on time. Very few owners or operators of CH or 4WT received formal training on how to use them. Among individuals who had received training, nearly all were trained by machinery supply businesses. Fees charged by outsourcers have remained stable or become cheaper in real terms, indicating the existence of competitive markets. CH enterprises initially served local markets but have expanded their geographical coverage over time, from a ‘core’ of irrigated paddy cultivating areas around Shwebo to other areas of the Dry Zone, the Delta and Bago. Provision of 4WT outsourcing services is much more localized than CH outsourcing. New specialized economic actors and markets for services have emerged extremely quickly in response to opportunities created by the growth of agricultural machinery outsourcing in the areas of: (1) 3rd party transport services; (2) brokers organizing groups of clients; (3) skilled machine operators. Transport logistics from 3rd party providers have lowered entry barriers into CH outsourcing by removing the need to own or operate vehicles used to transport CH. This makes it possible for CH outsourcers to offer services in distant locations without having to visit them in person Brokers acting as intermediaries between prospective service users and CH outsourcing enterprises have largely replaced self-organized groups, conferring advantages to both CH outsourcing enterprises and their customers. CH outsourcers have replaced their own labor with that of hired machine operators, freeing up their own time to engage in activities such as farming or non-farm business.